2017
DOI: 10.25179/tjem.2017-56505
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Diabetes and Obesity in Turkey

Abstract: Purpose: Diabetes mellitus (DM) and obesity (OB) are rising problems globally, and are also rapidly growing health issues in Turkey. The lack of a proper public awareness has worsened the situation, thereby hampering the implementation of preventive measures. The aim of the present study was to evaluate a questionnaire, speci cally designed for measuring the level of awareness of the general Turkish population on DM and OB. Material and Method: The International Diabetes Federation (IDF) questionnaire was modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…According to this study, the prevalence of IGT, obesity, and central obesity was elevated to 106%, 40%, and 35%, respectively. Besides, age, hypertension, waist measurement, BMI, low level of education, living environment in women, as well as age, BMI, and hypertension in men, were found as independently associated with an increased prevalence of DM (21). The study of Kulkarni et al indicated that the modifiable measures of adiposity (BMI and WC) were associated with higher odds of diabetes than other risk score components (22).…”
Section: Discussionmentioning
confidence: 97%
“…According to this study, the prevalence of IGT, obesity, and central obesity was elevated to 106%, 40%, and 35%, respectively. Besides, age, hypertension, waist measurement, BMI, low level of education, living environment in women, as well as age, BMI, and hypertension in men, were found as independently associated with an increased prevalence of DM (21). The study of Kulkarni et al indicated that the modifiable measures of adiposity (BMI and WC) were associated with higher odds of diabetes than other risk score components (22).…”
Section: Discussionmentioning
confidence: 97%
“…Those who scored between 16 and 25 were grouped as those with high awareness. The questionnaire prepared by the International Diabetes Federation (IDF) in Dinççağ et al (2017) was prepared with modifications (12). In this study, the Cronbach's Alpha coefficient of the scale was found to be 0.902.…”
Section: Questions On Type 2 Diabetes Awareness Level and Behavioral ...mentioning
confidence: 96%
“…Knowledge and awareness of type 2 diabetes are also important for behaviour change (11). For example, it has been reported that raising awareness of type 2 diabetes may be a very important factor in the long-term prevention of type 2 diabetes (12). In addition, research shows that addressing modifiable risk factors such as obesity, diet and physical inactivity can delay the onset of the disease (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sum of the healthcare expenditure on diabetes was USD 966 billion (20-79 years) in 2021 due to the data of IDF which represented an 316% rise over the last 15 years (IDF, 2021). Correlatively to other countries, the prevalence of DM is on the rise enormously in Turkey (Dinççağ et al 2017). TURDEP-1 which is a cross-sectional survey was carried out in Turkey between 1997 and 1998, including a population of 24,788 adults whose were older than 20 years.…”
Section: Introductionmentioning
confidence: 99%